Estimated costs of advanced lung cancer care in a public reference hospital - Renata Erthal Knust; Margareth Crisóstomo Portela; Claudia Cristina de Aguiar Pereira; Guilherme Bastos Fortes (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To estimate the direct medical costs of advanced non-small cell lung cancer care. METHODS We assessed a cohort of 277 patients treated in the Brazilian National Cancer Institute in 2011. The costs were estimated from the perspective of the hospital as a service provider of reference for the Brazilian Unified Health System. The materials and procedures used were identified and quantified, per patient, and we assigned to them monetary values, consolidated in phases of the assistance defined. The analyses had a descriptive character with costs in Real (R$). RESULTS Overall, the cohort represented a cost of R$2,473,559.91, being 71.5% related to outpatient care and 28.5% to hospitalizations. In the outpatient care, costs with radiotherapy (34%) and chemotherapy (22%) predominated. The results pointed to lower costs in the initial phase of treatment (7.2%) and very high costs in the maintenance phase (61.6%). Finally, we identified statistically significant differences of average cost by age groups, education levels, physical performance, and histological type. CONCLUSIONS This study provides a current, useful, and relevant picture of the costs of patients with non-small cell lung cancer treated in a public hospital of reference and it provides information on the magnitude of the problem of cancer in the context of public health. The results confirm the importance of radiation treatment and hospitalizations as the main components of the cost of treatment. Despite some losses of follow-up, we assess that, for approximately 80% of the patients included in the study, the estimates presented herein are satisfactory for the care of the disease, from the perspective of a service provider of reference of the Brazilian Unified Health System, as it provides elements for the management of the service, as well as for studies that result in more rational forms of resource allocation.